Sanksi Pidana Undang-Undang Nomor 35 Tahun 2014 terhadap Tindak Pidana Anak - Reza Iswanto; Mhd Badri (Wajah Hukum, 2022)
The death penalty only applies to ordinary crimes, while the death penalty is not imposed for the crime of killing people (in this case children). Judging from the behavior of the perpetrator, the perpetrator must be sentenced to death in accordance with the act of taking the life of a child. The research method used in this study is normative juridical so that it only examines the contents of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection which is descriptive and sources are primary, secondary and tertiary data sources. In this study, using a statutory approach and data collection techniques, namely document studies and data analysis, namely qualitative analysis. The results of this study explain that the regulation of criminal sanctions in Law Number 35 of 2014 against child crimes has been regulated in Article 80 paragraph (3) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Protection Children and in the future the criminal sanctions of Law Number 35 of 2014 against child crimes are that the death penalty must be applied to perpetrators of crimes who have eliminated/died the child as a victim.